Management of leaf blight of Chrysanthemum with compost teas (SAARC Journal of Agriculture, 2014)
Chrysanthemum (Chrysanthemum morifolium Ramil) is an important flower crop, being affected by leaf blight caused by Alternaria alternata (Fries) Keissler, a serious disease affecting the flower yield. The present studies were carried out to derive a management strategy with compost teas. The compost teas Vermicompost (CT-1), Vermicompost + Pseudomonas fluorescens1% (CT-2), Vermicompost  + Trichoderma viride1% (CT-3), Dung75% + Paddy Straw25% (CT-4), Dung75% + Paddy Straw25% + Pseudomonas fluorescens1% (CT-5), Dung75% + Paddy Straw25% +Trichoderma viride1% (CT-6), Dung75% + Neem Powder20% + Fish meal5% (CT-7), Dung75% + Neem Powder20% + Fish meal5% + Pseudomonas fluorescens1% (CT-8) and Dung75% + Neem Powder20% + Fish meal5% + Trichoderma viride1% (CT-9) were tested against the mycelia growth  and spore germination of pathogen, and against disease under field conditions. Compost teas that were sterilized by filtration were prefixed with S where ever necessary. Compost teas were effective in inhibiting the mycelia growth and spore germination. In single spray treatment the percent disease index varied from 9% (CT-8) to 21.34% (CT-4), in two spray treatments 8.69% (SCT-6) to 13.34% (CT-7) and in 3 sprays treatment 4.67% (CT-6) to 11.2% (SCT-1). Treatments CT-6 (4.67%), SCT-5 (4.75%) SCT-6 (6.45%), SCT-7 (5.85%) was superior to fungicide Iprodione 25% + Carbendazim 25%. The treatment CT-6 was most effective to increase the flower yield. DOI: http://dx.doi.org/10.3329/sja.v12i1.21112 SAARC J. Agri., 12(1): 48-61 (2014)